2011
DOI: 10.1177/0269215511412800
|View full text |Cite
|
Sign up to set email alerts
|

Health benefits of a view of nature through the window: a quasi-experimental study of patients in a residential rehabilitation center

Abstract: An unobstructed bedroom view to natural surroundings appears to have better supported improvement in self-reported physical and mental health during a residential rehabilitation programme, although the degree of change varied with gender and diagnostic group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
63
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 135 publications
(70 citation statements)
references
References 21 publications
2
63
0
4
Order By: Relevance
“…Donovan et al (2013) found evidence to suggest that areas subjected to a loss of trees owing to disease had increased mortality due to lower-respiratory-tract and cardiovascular illnesses. Further, in a study by Raanaas et al (2012), patients of a residential rehabilitation programme self-reported a better physical and mental health if their bedroom had a view of natural surroundings. Finally, green buildings have higher light levels, greater access to windows, conditions associated with thermal comfort, and fewer airborne particulates with occupants reporting a lower frequency of visual and physical discomfort symptoms, better mood, and better sleep quality (Newsham et al 2013).…”
Section: General Health Benefitsmentioning
confidence: 99%
“…Donovan et al (2013) found evidence to suggest that areas subjected to a loss of trees owing to disease had increased mortality due to lower-respiratory-tract and cardiovascular illnesses. Further, in a study by Raanaas et al (2012), patients of a residential rehabilitation programme self-reported a better physical and mental health if their bedroom had a view of natural surroundings. Finally, green buildings have higher light levels, greater access to windows, conditions associated with thermal comfort, and fewer airborne particulates with occupants reporting a lower frequency of visual and physical discomfort symptoms, better mood, and better sleep quality (Newsham et al 2013).…”
Section: General Health Benefitsmentioning
confidence: 99%
“…There are many examples: screens showing nature imagery in waiting rooms for people about to give blood (Ulrich, Simons, & Miles, 2003), large landscape scenes presented on curtains around beds where patients laid while undergoing an uncomfortable bronchoscopy procedure (Diette, Lechtzin, Haponik, Devrotes, & Rubin, 2003), window views of trees from a hospital room in which patients spent several days recovering from surgery (Ulrich, 1984), window views over the surrounding landscape from the rooms of patients going through rehabilitation programs several weeks in length (Raanaas, Patil, & Hartig, 2012), and outdoor garden spaces at assisted living facilities in which elderly people were receiving daily care during the remainder of their lives (Dahlkvist et al, 2016;Ottosson & Grahn, 2005).…”
Section: Health Care Environmentsmentioning
confidence: 99%
“…Klinik çalışmalarında, teşhis-tanı-tedavi işlemleri sırasında doğa görüntüsü ve seslerinin birlikte hastalarda ağrı ve endişenin önemli ölçüde azaldığı (Lechtzin et al2010, Diette et al 2003, ameliyat sonrası iyileşme sürecinde hastane odasının penceresinden bir peyzaj alanının (Ulrich 1984, Hartig et al 2003, Raanaas et al 2012, Donovan et al 2013) görülmesi daha az ağrı kesici kullanımına neden olduğu ve hastaların duygu durumlarına ve iyileşme süreçlerine olumlu katkı sağladığı tespit edilmiştir. Önceki çalışmalarda, stres azaltma teorisi doğrultusunda doğal manzara konulu fotoğraflar ve videolar görüntülemenin stresin indikatörleri olan cilt kondüktansı (iletkenlik), kalp hızı ve diğer fizyolojik belirtilerin azaltmasında etken olduğu tespit edilmiştir (Gladwell et al 2012, Laumann et al 2003, Ulrich et al 1991.…”
Section: Sonuç Ve Tartişmaunclassified
“…Bu anlamda, yarı-deneysel örneklem alan çalışmalarında, hastaların tedavi süreçlerinde ya da sırasında doğaya ilişkin görsel materyalleri izlemelerinin beden ve ruh sağlıkları ile stres düzeylerinde olumlu etkileri olduğuna ilişkin bulgular dikkat çekicidir (Raanaas et al 2012, Beukeboom 2012, Drahota 2012.…”
Section: Introductionunclassified